Traiter l’échec des étudiants dans une université française du bout du monde : constats et propositions de ses acteurs - Martine Pons-Desoutter (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
To reduce the massive failure of its first year undergraduate students, the University of New Caledonia, along with its Help Office to Professional Insertion, conducted a survey among its actors: students and teachers. This study aimed to identify strategic areas in order to suggest improvements in a concerted effort. This article outlines the main axes identified by these actors in the educational field, in the light of research works carried in other French universities. If these axes are not far from actions that mobilize pedagogy services of universities, their implementation still requires a preliminary work on the look given by teachers over new students.